"The Goals Remain Elusive": Using Drawings to Examine Shifts in Teachers' Mental Models Before and After an NGSS Professional Learning Experience. Issue 5 (3rd July 2020) - Sherwood, Carrie-Anne
ABSTRACT: Teachers' ability to effectively enact the ambitious vision of the NGSS depends on their understanding of the conceptual and instructional shifts required, and their interpretation of how to implement these shifts in their classrooms. Thus, understanding teachers' practical knowledge regarding the shifts is an important step in supporting them to effectively implement the NGSS vision. This study used a mental models framework and teacher drawings to examine the practical knowledge of 22 in-service secondary science teachers before and after professional development that was designed to support them to understand and make incremental instructional shifts aligned with the NGSS. Findings indicate that teachers' mental models shifted in two promising ways. First, teachers recognized that their roles and their students' roles would need to change, and second, the doing of science looks and sounds different than what was traditionally done in their classrooms. However, findings also suggest that teachers struggled to reconcile new ideas from the PD with their previous mental models of their classroom practice. These findings are significant because they indicate, teachers may have more fully-formed mental models for what science teaching and learning looks and sounds like when it is focused on what most would traditionally think of as classroom science doing (e.g., "doing labs"), or when it includes traditional knowledge dissemination structures (e.g., lectures). This has important implications for science teacher educators and researchers, which will be discussed.